Pemetaan Tipologi Pesantren di Desa Santri: Studi Kasus Desa Ganjaran Kabupaten Malang - Abdurrahman, Abdurrahman; Arifin, Badrul (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
Islamic boarding schools (pesantren) are the oldest educational institutions in Indonesia, having undergone continuous development and transformation while maintaining their relevance within the national education system. One area with a high concentration of pesantren is Ganjaran Village, located in Gondanglegi Subdistrict, Malang Regency, widely recognized as a “Santri Village.” However, academic studies that specifically identify and classify the typology of pesantren in this area remain limited. This study, therefore, aims to comprehensively inventory all pesantren in Ganjaran Village and examine their typologies based on established theories of Islamic boarding school education and their alignment with national educational regulations. A qualitative descriptive method with a case study approach was employed. Data were collected through village archival documentation, official pesantren websites, internal institutional documents, in-depth interviews, and field observations. Data analysis was conducted using pattern matching and cross-case synthesis techniques to identify classification patterns based on historical dimensions, learning systems, leadership, legal status, and socio-religious influence. The findings reveal the presence of 24 active pesantren in Ganjaran Village. The oldest was established in 1908, and the most recent in 2023. All institutions follow a traditional (salafiyah) system, with most still under the leadership of their respective founders. While the majority are equipped with relatively complete facilities, some lack formal operational permits. Generally, most pesantren exert considerable religious influence extending beyond Java Island, although none have more than one thousand resident students. These findings contribute to the academic understanding of pesantren diversity within a single village context and offer valuable insights for the development of community-based Islamic education policies.